Application of Hybrid Real-Time Power System Simulator for Designing and Researching of Relay Protection and Automation; IOP Conference Series: Materials Science and Engineering; Vol. 93: Modern Technique and Technologies (MTT'2015) - Borovikov Y. S. Yuri Sergeevich (Power industry, 2015)
Title screen